The Analysis of Criticism of Newspaper by Jokowi & Joe Biden regarding the Development of Covid-19 in the IDN Times and NY Times Online Media: Cross-Cultural Pragmatic Studies: Cross-Cultural Pragmatic Studies - Melisa Wulan Purnama; Ni Wayan Sartini (UIN Salatiga, 2023)
The research entitled